Political and ideological training: Gramsci's "schools" - Lussana, Fiamma (International Gramsci Journal, 2025)
The political-pedagogical model has always had great relevance in Gramsci’s political and intellectual biography. When he arrived in Turin from Sardinia to attend university, Gramsci made a fundamental discovery: that knowledge and education are formidable instruments of emancipation for the popular masses. He continued to pay great attention to the experiences of political and ideological education during his stay in Moscow, in Vienna, after his return to Italy, and during his years in prison. Using the documents held at the Gramsci Foundation in Rome and the accounts of Italian students who attended the Petrograd Schools of Ideological Education, this essay aims to shed light on Gramsci’s role in establishing the first Schools of Political Education under the auspices of the Communist International, as well as his work in organising the most significant schools of political education.